Complexity of archaeological research and natural scientific studies in identifying the location of ashlama-saray, the country palace of the crimean khans - BOCHAROV, S.G; SITDIKOV, A.G; LATYPOV, N.R; FAHRUTDINOV, R.R (Utopía y Praxis Latinoamericana, 2019)
ABSTRACT The article dwells on the results of the search for the archeological site – Ashlama-Saray – the country palace of the Crimean Khans. The palace was built in the second half of the 17th century. At the end of the 18th century, the main buildings of the palace were reconstructed. Currently, the ruins of the palace are not identified on the surface. The location of this monument was determined by a general plan of Bakhchisaray city. During the series of archaeological and natural-scientific works carried out in 2015–2016, this palace was precisely localized in the valley of Ashlama-Dere. RESUMEN El artículo se centra en los resultados de la búsqueda del sitio arqueológico - Ashlama-Saray - palacio de los Khans de Crimea. El palacio fue construido en la segunda mitad del siglo XVII. A finales del siglo XVIII, los principales edificios del palacio fueron reconstruidos. Actualmente, las ruinas del palacio no están identificadas en la superficie. La ubicación de este monumento fue determinada por el plan general de la ciudad de Bakhchisaray. Durante la serie de trabajos arqueológicos y científicos naturales llevados a cabo en 2015-2016, este palacio fue localizado precisamente en el valle de Ashlama-Dere.